Exercise reduces the anxiogenic effects of meta-chlorophenylpiperazine: The role of 5-HT2C receptors in the bed nucleus of the stria terminalis - Fox, James H.; Boucher, Melissa N.; Abedrabbo, Khalil S.; Hare, Brendan D.; Grimmig, Bethany A.; Falls, William A.; Hammack, Sayamwong E. (Frontiers in Synaptic Neuroscience, 2023)
Two weeks of voluntary exercise in group-housed mice produces a reduction in anxiety-like behaviors across a number of different measures, including a reduction in the anxiety levels typically produced by the anxiogenic serotonergic drug m-chlorophenylpiperazine (mCPP), an agonist at 5-HT2c/2b receptors. We have previously demonstrated that 2-weeks of voluntary exercise blunted the anxiogenic effects of systemic mCPP, and we have also shown that mCPP infused into the bed nucleus of the stria terminalis (BNST) is anxiogenic. Here we follow up on these reports and demonstrate that 2-weeks of voluntary exercise blocks the anxiogenic effect of BNST mCPP at multiple doses. We demonstrate that mCPP administered into amygdala subregions or the dorsal hippocampus was not able to increase acoustic startle responding produced, and lesions of the BNST prevented the anxiogenic effect of systemically administered mCPP. Together these results suggest that the BNST is a critical site of action for the effects of exercise on mCPP. In addition, the anxiogenic effects of BNST-infused mCPP were blunted by the selective 5-HT2c antagonist SB242084, and exercise reduced 5-HT2C transcripts in the BNST. Together these data suggest that exercise may reduce 5-HT2C receptor function in the BNST, which may, in part, explain some of the anxiolytic effects associated with wheel running.